Uso de substâncias psicoativas lícitas por estudantes de enfermagem - Neves, Fernanda Borba; Carvalho, Ana Carolina de Lima; Silva, Luiz Rubio Martins; Braz, Marcia Ribeiro (Revista Interdisciplinar do Direito - Faculdade de Direito de Valença, 2017)
.